Zum Gedenken an Emil Artin (1898-1962) - Der Präsident der Universität Hamburg (Hamburger Universitätsreden Neue Folge, 2006)
Emil Artin (1898-1962): his scientific results in mathematics attracted general attention and had far-reaching consequences for research. The brilliant style of his lectures made him a virtuoso thinker and a sought-after teacher. Artin was full professor at the Mathematical Seminar at the University of Hamburg. When the Nazis retired him in 1937 due to the "Nuremberg laws", he emigrated to the USA. It was not until 1958 that he returned to the University of Hamburg.